Creosoteerfabriek Feijenoord. Kopie van origineel in Gemeentelijke Archiefdienst Rotterdam (neg.: G 3579) (1869)
Creosoteerfabriek Feijenoord. Kopie van origineel in Gemeentelijke Archiefdienst Rotterdam (neg.: G 3579).